2018
DOI: 10.11622/smedj.2017106
|View full text |Cite
|
Sign up to set email alerts
|

Hemithyroidectomy for low-risk follicular carcinoma of the thyroid: results from a regional hospital

Abstract: Introduction: Excellent outcome after conservative thyroid surgery for low-risk follicular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In line with the authors’ opinion, I have declared that I am a partisan advocate of hemithyroidectomy for low-risk DTC. Nevertheless, I have some comments on the article by Nickel et al First, the authors have not lucidly described whether central compartment dissection was performed in addition to total thyroidectomy.…”
supporting
confidence: 59%
“…In line with the authors’ opinion, I have declared that I am a partisan advocate of hemithyroidectomy for low-risk DTC. Nevertheless, I have some comments on the article by Nickel et al First, the authors have not lucidly described whether central compartment dissection was performed in addition to total thyroidectomy.…”
supporting
confidence: 59%
“…Whether these patients require completion thyroidectomy or further RAI is controversial. Some surgeons advocate that TT should be recommended for all patients with FTC because of its high risk of distant metastases [5][6][7], while others thought routine completion thyroidectomy and RAI were unnecessary because they found that the extent of surgery had no significant influence on the prognosis of low-risk FTC [8][9][10]. The recent American Thyroid Association (ATA) guidelines recommend that LT may be an adequate primary surgical procedure for low-risk PTC and FTC with a tumor size not exceeding 40 mm, while a near-total or TT should be the initial treatment for PTC and FTC patients with tumor size [ 40 mm [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroglobulin (Tg) was used as a tumor marker for surveillance. Although monitoring with Tg following total thyroidectomy is widely practiced, its usage or benefit is dubious for lobectomy . Would the authors elaborate the efficacy of Tg for thyroid cancer after partial thyroidectomy?…”
mentioning
confidence: 99%